Urban biodiversity as a symptom of a sustainable city. Case study of the Yanuncay area in Cuenca, Ecuador - Cordero, Paula; Vanegas, Sebastián; Hermida, María Augusta (Maskana, 2015)
By testing the situation of urban biodiversity and green spaces in the area of Yanuncay in Cuenca (Ecuador), we intended to reveal peculiarities of co-determination between biodiversity and green areas within the city. Six indicators and three indexes were calculated and showed alarmingly low levels, suggesting the need for immediate action to recover the lost biodiversity. For example, in the case of the indicator of Permeability of Public Land, 83.53% is not permeable; in terms of the Proximity to Green Spaces, 98.82% of the study area does not approach the minimum target; regarding the calculation of Density of Trees in each Segment of Road, 98.83% of the sections have not enough trees. An important contribution of this work is the construction of the Green Urban Index (IVU) that combines two indicators Green Area per Person with Simultaneous Proximity to Three Types of Green Spaces, so that an integrated evaluation can be given to both: namely the quantity and the coverage, and the influence, at different scales, that these areas have over people. With this index we see that 91.76% of the area does not meet the minimum value. This data allows us to state that the present city and its production of green areas do not contribute to ecological sustainability and hence urban biodiversity. If urgent effective changes are not proposed to the actual city model, these values will become even more alarming.